2005
DOI: 10.1007/s10541-005-0266-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Superoxide Dismutase Activity and Peroxynitrite Content in Rat Peritoneal Macrophages Exposed to He-Ne Laser Radiation

Abstract: The formation of reactive oxygen and nitrogen species by rat peritoneal macrophages induced by a low-intensity He-Ne laser radiation (LR) was studied in this work. It was found that the formation of reactive oxygen species, nitric oxide, and peroxynitrite as well as changes in the activity of superoxide dismutase (SOD) depended to a large extent on the LR dose. In particular, it was found that activation of SOD at low LR doses was accompanied by nitric oxide level increase, while the level of peroxynitrite sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Previous in vitro studies by Klebanov's group [27] showed that HeNe laser irradiation increased NO secretion from macrophages to a maximum of 80% with 0.6 J/cm 2 [26], and 75% with 0.36 J/cm 2 . These results are compatible with the %increase in NO secretion found in the current study (60-100%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies by Klebanov's group [27] showed that HeNe laser irradiation increased NO secretion from macrophages to a maximum of 80% with 0.6 J/cm 2 [26], and 75% with 0.36 J/cm 2 . These results are compatible with the %increase in NO secretion found in the current study (60-100%).…”
Section: Discussionmentioning
confidence: 99%
“…The collagen deposition in irradiated animals and the decrease of mononuclear cells on days 3 through 5 after wounding could be explained by the capacity of the laser locally to increase enzyme activity of mononuclear cells and fibroblasts. 8,[21][22][23] On days 5 through 7, a predominance of fusiform cells showing smooth muscle actin-a and desmin was observed by electron microscopy in animals exposed to LLLT. We assume that a light-source stimulus not only increased the number of myofibroblasts on the wound, but also activated secretory functions.…”
Section: Marchionni Et Almentioning
confidence: 97%
“…The resulting reduction of the pH-level in the myocardium tissues inhibits SOD activity. Low-intensive He-Ne laser radiation enhances SOD activity in vitro 17,18 . Relatively wide band luminescent red light (λ peak = 630 nm) could cause the similar effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia of heart muscle causes dramatic changes of the functional activity of myocardium 12 , damages of membranes of cardiac myocytes [13][14][15] and the increase of LPO level in the heart tissues [14][15][16] . At the same time, it is well known 17,18 that red laser light can reactivate the SOD enzyme and control activity of the lipid peroxidation processes in the sample tissues. These phenomena might be considered as the key mechanisms of the observed photo therapeutic effect of red light on living tissues.…”
Section: Introductionmentioning
confidence: 99%